PENGARUH KARAT TERHADAP KETANGGUHAN MARETIAL BAJA UNTUK JEMBATAN - Fauzri Fahimuddin (Jurnal Ilmiah Poli Rekayasa, 2022)
Rust is a major problem in steel bridge construction because it has the potential to affect the integrity of the structure and is also an important consideration for inspection and maintenance programs. This study shows the results of laboratory tests on the effect of rust within 1 to 9 weeks on fracture toughness as one of the important mechanical properties of steel bridge elements. The specimens in this study were made of SM 490 type, steel commonly used for bridge construction. Rustless and rusted specimens were used with varying degrees of exposure after immersion in acid solution to simulate the rate of rust. The effect of rust rate on fracture toughness due to mass loss was studied. The fracture toughness of each specimen was monitored for those specimens with exposure periods of 1 week, 2 weeks, 3 weeks, 4 weeks, and 9 weeks to test their effect on toughness. The results of this study showed that there was no significant reduction in the rusting duration of 1 week, 2 weeks, 3 weeks, 4 weeks, and 9 weeks of fracture toughness. Rusting and testing activity for the long term is still ongoing and will be continued, as the results of this study greatly help bridge designers and asset managers to better model rust inspection and maintenance plans and assess the structural integrity of steel bridges affected by rust more accurately.